A new class of rational multistep methods for the numerical solution of first order initial value problems - Teh, Yuan Ying; Yaacob, Nazeeruddin; Alias, Norma (Jabatan Matematik Universiti Teknologi Malaysia, 2011)
In this paper, we have developed a new class of 2-step rational multistep methods (RMMs) in second to fifth order of accuracy.We have presented the developments of these RMMs, as well as the local truncation error and stability analysis for each RMM that we have developed.Numerical experiments have shown that all RMMs presented in this paper are suitable to solve initial value problem of various dimensions and also stiff problems.